Estudo da prevalência de disfunção craniomandibular segundo o índice de Helkimo tendo como variáveis: sexo, faixa etária e indivíduos tratados ou não ortodonticamente - Lima, Dimas Renó de [UNESP] (1995)
One hundred non-patient dentistry students aged 17 to 25, were interviewed through questionnaire and were clinically examined in order to asses the prevalence and degree of severtty of Craniomandibular Dysfunction, through indeces which are subdivided into three classes: anaminestic index, clinical dysfunction index, and occlusal index. The following variables were introduced to the original indeces: sex, age, and whether the subjects had or had not received orthodontic treatment. The results showed that 42% of the subjects presented mild subjective symptoms whereas, no one showed severe subjective symptoms. Women, as well as the older subjects, showed a higher trend to presenting more subjective complaints. Subjects, whether treated orthodontically or not, showed a similar trend to having dysfunction symptoms. Fifty-six per cent of the subjects presented some score of clinical dysfunction, 25% of them showed moderate or severe clinical dysfunction. Women showed a statistically significant higher index. The older subjects trented to have indeces with more severe degrees. Orthodontic treatment suggested to have no influence on the clinical dysfunction index. Sixty-six per cent of the subjects showed a mild occlusal index and 11% a severe occlusal index. Sex, age, and orthodontic treatment did not show any significant difference as to the presence or absence of malocclusion